Argumentative Trends in Opinion Columns in Two High Circulation Colombian Newspapers (2020)
Taking into account the importance of the media for society and the role of the academy in the training of reflexive and critical subjects, this article of reflection, derived from a doctoral tesis that is still under construction in the teaching of understanding of texts of argumentative typology, intends to identify, from a historical-hermeneutic análisis and in a corpus of more than  543 opinion columns, whose theme revolves around  higher education in Colombia during the post-conflict period (2016-2018), the main argumentative tendencies that stand out there and those used by several of the authors of the two must important newspapers of mass circulation in Colombia (El Tiempo and El Espectador). The results of the investigation show the predominance of certain types of reasonings (pragmatic, cause-effect, authority, example and probable) that are analyzed considering ancient and neo-rhetoric; thanks to them, the authors seek to gain the adhesión of the members of the discursive communities to which they are directed.